(untitled) - Campbell, Richard (Boston, 2004)
Breaking the mold of traditional mass communication textbooks, Richard Campbell’s Media & Culture goes beyond the basic facts and presents students with a critical and cultural perspective on the media. Campbell uses a unique five-stage critical thinking process to help students examine the forces that shape the mass media and become active participants in the media. Media & Culture’s integrated cultural perspective focuses on the reciprocal relationship between the mass media and our shared culture — how cultural trends affect our media and how historical developments, technology, and key media leaders have shaped our society. Completing the full picture of the mass media is the text’s in-depth coverage of the history, structure, and economics of each industry. Continuing the tradition of cutting-edge content, the 2009 Update includes the most current media trends and developments
Keywords: Mass media and culture,Popular culture,Truyền thông; United States,United States